Use of predator exclusion cages to enhance Orbicella faveolata micro-fragment survivorship and growth during restoration - Raker, Catherine; Olmeda-Saldaña, Manuel; Williams, Stacey M.; Weil, Ernesto; Prada, Carlos (Frontiers in Marine Science, 2023)
As coral reefs face increasing threats from a variety of stressors, coral restoration has become an important tool to aid coral populations. A novel strategy for restoring boulder corals is microfragmentation, which may enhance coral growth by at least five times, depending on species and conditions. However, mortality rates are still significant during the early weeks after transplanting microfragments to impacted areas. We examined the effects of predation after transplanting fragments by caging Orbicella faveolata microfragments and testing if field survival rates would increase after an acclimation period. We tracked the health and growth of ten genotypes across different acclimation periods from a control group of no acclimation (0 months) to full acclimation (4 months). After four months, we presented a mix of acclimated and unacclimated corals to reef predators. Coral survivorship was highest in acclimation cages (near 100%) compared to the field (p < 0.001), with significant growth differences across genotypes (p < 0.001). Microfragments also grew more in acclimation cages (p < 0.001), with rates slowing down in the first two months after being planted into the substrate. Microfragments that had been acclimated for longer than one month also showed comparatively higher survival rates, further supporting the importance of acclimation during restoration. These results suggest caging fragments boost coral survival during initial stages of restoration by > 50% and increase the persistence of transplanted fragments. Results also highlight the importance of identifying and prioritizing genotypes with high survival and growth rates. Beyond coral restoration, results demonstrate the possible negative ecological effects of corallivores, particularly parrotfishes, on recent transplants of fragments.